2011
DOI: 10.1523/jneurosci.6054-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Currents Modulate the Synaptic Input–Output Functions of Neurons in the Dorsal Nucleus of the Lateral Lemniscus in Mongolian Gerbils

Abstract: Neurons in the dorsal nucleus of the lateral lemniscus (DNLL) receive excitatory and inhibitory inputs from the superior olivary complex (SOC) and convey GABAergic inhibition to the contralateral DNLL and the inferior colliculi. Unlike the fast glycinergic inhibition in the SOC, this GABAergic inhibition outlasts auditory stimulation by tens of milliseconds. Two mechanisms have been postulated to explain this persistent inhibition. One, an "integration-based" mechanism, suggests that postsynaptic excitatory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 34 publications
(63 reference statements)
6
35
0
Order By: Relevance
“…These membrane parameters were analyzed from the average voltage response to 40 -60 repetitions of 200 ms-long step current injections of Ϫ10 pA ( Fig. 1A; n ϭ 75) (Ammer et al 2012;Berger et al 2014;Couchman et al 2010;Porres et al 2011). The use of such a small current amplitude kept the resulting voltage deflection minimal and hence minimized the activation or deactivation of additional voltage-dependent conductances close to the neuron's resting state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These membrane parameters were analyzed from the average voltage response to 40 -60 repetitions of 200 ms-long step current injections of Ϫ10 pA ( Fig. 1A; n ϭ 75) (Ammer et al 2012;Berger et al 2014;Couchman et al 2010;Porres et al 2011). The use of such a small current amplitude kept the resulting voltage deflection minimal and hence minimized the activation or deactivation of additional voltage-dependent conductances close to the neuron's resting state.…”
Section: Resultsmentioning
confidence: 99%
“…So far, we characterized the developmental changes and relative contributions of passive and active conductances to the firing pattern using step protocols between 200 and 500 ms. However, action potentials in the auditory brain stem are usually triggered by 0.5-2 ms fast synaptic ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid conductances (Ammer et al 2012;Couchman et al 2010;Porres et al 2011;Taschenberger and von Gersdorff 2000;Yang and Xu-Friedman 2009) rather than by prolonged depolarization plateaus. Thus the development of the relevant action-potential properties cannot be extracted using long current injections.…”
Section: Resultsmentioning
confidence: 99%
“…Although NMDARs are strongly developmentally downregulated in the ITD circuit (Futai et al 2001;Zhou and Parks 1993), recent work indicates that NMDARs still play a functional role at mature stages (Caicedo and Eybalin 1999;Porres et al 2011;Steinert et al 2010). To investigate a possible contribution at mature MSO cells, functional NMDAR expression was mapped along their dendrites with UV uncaging of MNI-Glu (n ϭ 14, P30 -35).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fricker and Miles (2000) showed a decrease in EPSP area when blocked by AP5 in hippocampal pyramidal cells, and Connelly et al (2016) showed strong EPSP amplification by NMDA currents in thalamocortical neurons. In addition, Porres et al (2011) observed an EPSP decay phase prolongation in neurons of the dorsal nucleus of the lateral lemniscus caused by NMDA currents.…”
Section: Negative Slope Conductance Amplifies Postsynaptic Potentialsmentioning
confidence: 93%